Singing out Strange Days - Pisk Marjeta (Journal of Ethnology and Folkloristics, 2025)
In Slovenia, group singing played an important role in times of political change and crisis. It was deliberately used in times of uncertainty, when there was a greater need for cohesion, such as during the First World War, the Second World War and the Covid-19 pandemic. The songs that were most widely used at a given time reflected the emotional needs and desires of people in precarious situations. With the advent of new technologies, new modalities of group singing, such as singing at a distance and virtual choirs were enabled. During the Covid-19 pandemic lock-down, group singing was realised via online tools, which has a number of limitations. Using three examples from times of uncertainty the specific characteristics of group singing that allow it to thrive in times of crisis are analysed.